Application of Problem Based Learning Model Based on Reading to Learn (R2L) Method to Improve Students' Science HOTS-Literacy Ability on Chemical Bonding Material - Khalisa Fahira Ifkar; Iis Siti Jahro (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Application of Problem Based Learning Model based on Reading to Learn (R2L) Method to Improving Students' Science HOTS-Literacy Ability on Chemical Bonding Material. This study aims to determine the improvement of students' science HOTS-Literacy skills after the application of Problem Based Learning Model based on Reading to Learn (R2L) method on chemical bonding material. This research was conducted using a quasi-experimental approach, namely a pretest-posttest design with a control group. In its implementation, the study involved two experimental class groups that received learning through the PBL model based on the R2L method and the control class that received learning with the PBL model without the R2L method. Based on the research results, the hypothesis obtained sig 0.00 <0.05 which means the alternative hypothesis (Ha) is accepted. This shows that the increase in students' science HOTS-Literacy ability applying the R2L-based PBL model (n-gain = 67.99%) is higher than the control class that applies the PBL model without R2L-based (n-gain = 50.99%).